Late Quaternary Landscape Evolution of the Swale-Ure Washlands, North Yorkshire - Mitchell, Wishart; Bridgland, David; Innes, Jim (Historic England, 2011)
Reporting on a multi-disciplinary project this book seeks to reconstruct the history since the last glaciation of the area between and including the middle reaches of the Rivers Swale and Ure in Yorkshire. Included in this history are both natural changes, determined from studies of landforms and sediments, and human-induced changes, recorded in archaeological and geo-archaeological records. The work is set in the context of previous research and pre-existing knowledge, outlined in an introductory chapter. Key methods used include geomorphological mapping and the study of sediment exposures, both aimed at reconstructing the final phases of glaciation and then the melting of the ice and its replacement by the post-glacial rivers, as well as the use of fossil materials to reconstruct the post-glacial record, both of natural change and increasing anthropogenic impacts.